INTEGRASI LITERASI KRITIS DALAM PENGAJARAN BAHASA: STRATEGI INOVATIF UNTUK MENGEMBANGKAN PEMIKIRAN REFLEKTIF - Firdaus, Laila; Mayuni, Ilza (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2025)
This study explores critical literacy strategies, reflective abilities, and intercultural competence in language teaching to develop critical, reflective, and adaptive students. Research objectives include identifying key barriers, developing innovative strategies, and practical solutions for integrating critical literacy in education. The research uses a qualitative approach based on literature review, best practice analysis, and theoretical case studies. Data were analyzed through a descriptive-critical approach and thematic synthesis to produce a holistic framework. The research results show that the main obstacles include limited understanding of the socio-cultural context, difficulty analyzing multimodal texts, and embedded cultural stereotypes. Strategies such as authentic text discussions on socio-cultural themes, multimodal discourse analysis, and cross-cultural simulations have proven effective in improving students' critical literacy skills, reflective abilities, and intercultural sensitivity. This approach allows students to understand global issues in depth, develop analytical skills, and adapt to different cultural norms. The novelty of this study lies in the integration of critical literacy, multidimensional reflection, and intercultural competence in one holistic learning framework. This approach is relevant to facing the challenges of globalization and preparing students to become individuals who are responsive to an ever-evolving world. These findings provide an important contribution to the development of inclusive education that is relevant to the needs of the 21st century.